Segmenting the right ventricle cavity from 4D echocardiography images for stroke volume measurement - Abboud, Anas A. (2014)
Quantitative measurement is an important indicator for assessment, diagnosing and decision making by the specialists. Therefore, Computer Aided (or assisted) Diagnosis systems (CAD) are increasingly affordable; it has been incorporated in routine clinical practice. In this research we address right ventricle (RV) assessment by measuring the stroke volume of the ventricle. This can be done through, segmenting RV cavity, and determining the End-Diastolic (ED) and End- Systolic (ES) stages of the cardiac cycle. Then measure the volume at ED and ES stages to compute the stroke volume. Viewing the whole RV cavity structure is also may give initial assessment for the cavity abnormality. By reviewing most of the previous work in the literature, there are different methods used to segment the right ventricle (RV) cavity, such as boundary based detection, texture, and regional segmentation methods. All of these methods focused on a manual or semi-automatic extraction of the RV structure. It is obvious that there is a lack of concentration on the multifarious structure of the RV cavity (apex, moderator band, trabecular, and Inflow-Outflow regions). The ED and ES stages for the cavity are determined manually by review of individual image phases of the cavity, and/or tracking the tricuspid valve. In the other hand, the current 3D reconstruction method of the RV structure is built by original for the left ventricle. Thus it doesn’t represent the actual structure of the RV cavity. New algorithms are needed to assess the abnormality of the right ventricle. This process can be done by accurate segmentation of the cavity, determination of the End-Diastolic and End-Systolic stages of the cardiac cycle, measuring the stroke volume, and reconstructing the three dimension model of the segmented region of the cavity for initial assessment of the abnormality. In this work, we propose a method for semi-automatic segmentation of the right ventricle to measure the stroke volume from four dimensions (4D) echocardiography, based on a novel analysing for the complex geometrical structure and function of the right ventricle. The right ventricle structure is simplified by slicing the right ventricle in 4D echocardiography images. Region growing technique is deployed to segment the cavity in each slice. This technique works automatically by detecting a seed point inside the region of interest (ROI), independently utilizing pre-knowledge of the region feature. Then start the iterative region growing segmentation process.Automatic detection for the End-Diastolic and End-Systolic stages of the cardiac cycle is introduced, by tracking the changes area of the segmented region of the cavity along one cardiac cycle. Disk summation principle is used to compute the volume of the segmented region in each slice. The resolution of the xMATREX array TEE transducer (X7-2t) is also estimated to measure the volume in millilitre unit. Then compute the cavity stroke volume by finding difference between the volume of the cavity at the ED and ES stages. The contours of the segmented region are extracted to generate the cloud of points (ℝ 3 ). Finally, generate three dimensions modelling for the segmented cavity by developing the normal feature approximation method for the cloud point, in order to accurately delineate the required object. The proposed method requires minimal user-initialization to determine the ROI and executions, which requires only few seconds for one time along the processing time. Comparisons of the segmentation, End-Diastolic and End-Systolic stages, stroke volume and the reconstructed 3D model; are provided with currently available software for left ventricle volume, function assessment and 3D modelling to validate the merit of the proposed work. The results of each step of process are satisfied high acceptance from the cardiologist experts in the qualitative validation, and a good accuracy in quantitative validation regarding to techniques.